The Role of Work Discipline, Islamic Work Ethics, Compensation in Shaping Job Satisfaction Among Muslim Employees - Hilman, Muhammad Ferizqo; Sekarsari, Meidiati (Research of Islamic Economics, 2025)
This study examines the impact of work discipline, Islamic work ethics, and compensation on the job satisfaction of Muslim employees in Tangerang City. Using a Saturated Sampling method, data were collected via a questionnaire and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method. The findings reveal that work discipline, Islamic work ethics, and compensation each have a positive and significant effect on job satisfaction. These factors are shown to be highly effective in enhancing job satisfaction among employees. The managerial implications suggest that improving work discipline, fostering Islamic work ethics, and offering fair and competitive compensation can significantly boost job satisfaction. This study contributes by highlighting the importance of these variables in shaping employee satisfaction, specifically within the context of Islamic values. Moreover, the predictive model developed through PLS-SEM offers organizations practical insights into creating fair, consistent policies that align with Islamic principles to enhance workplace satisfaction. These findings underscore the value of integrating ethical and equitable practices to improve the job satisfaction of Muslim employees in Tangerang City.